2007
DOI: 10.1063/1.2430917
|View full text |Cite
|
Sign up to set email alerts
|

Transparent amorphous indium zinc oxide thin-film transistors fabricated at room temperature

Abstract: The authors report on transparent thin-film transistors using amorphous indium zinc oxides for an active channel layer and gate-source-drain electrodes fabricated by rf magnetron sputtering at room temperature. The conducting properties of the amorphous indium zinc oxides were controlled by oxygen partial pressures in the sputtering ambient. An amorphous AlOx served as the gate dielectric oxide. Devices were realized that display a threshold voltage of 1.1V and an on/off ratio of ∼106 operated as a n-type enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Among these AOSs, the amorphous indium zinc oxide (a-IZO) is a good candidate for flexible TFTs and flexible electronic circuit applications. A-IZO exhibits a wide optical band gap (3.7 eV), high mobility (<60 cm 2 /V s), and resistivity between 10 −4 and 10 1 cm [9,10]. Several reports demonstrated that a-IZO films permit controllable conductivity and are appropriate for use as the active layers and source/drain electrodes in transparent TFTs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these AOSs, the amorphous indium zinc oxide (a-IZO) is a good candidate for flexible TFTs and flexible electronic circuit applications. A-IZO exhibits a wide optical band gap (3.7 eV), high mobility (<60 cm 2 /V s), and resistivity between 10 −4 and 10 1 cm [9,10]. Several reports demonstrated that a-IZO films permit controllable conductivity and are appropriate for use as the active layers and source/drain electrodes in transparent TFTs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…Most a-IZO films and a-IZO TFTs are prepared on glass substrates [9][10][11][12] or silicon wafer [13,14] using physical vapor deposition (PVD) techniques such as RF magnetron sputtering and pulsed laser deposition. These require expensive equipment and result in high manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ZnO thin films has attracted widely attention for a variety of optoelectronics and microelectronics applications [1][2][3][4][5][6][7][8], it can be widely used in transparent thin films transistors (TFTs), resistive random access memory (RRAM) devices [9], surface acoustic wave device and other fields. To accommodate the improvements such as decreased feature size, increased device speed and more intricate designs, each layer in the devices must be flatted.…”
Section: Introductionmentioning
confidence: 99%
“…Physical vapor deposition (PVD) is a common film deposition method, and its deposition mechanisms have been thoroughly studied [1][2][3][4]. In particular, sputtering deposition and pulsed laser deposition (PLD) have become widely used techniques for the deposition of thin films because of the advantages of a simple system setup, wide range of deposition conditions, wider choice of materials and higher instantaneous deposition rates.…”
Section: Introductionmentioning
confidence: 99%